“ATTITUDE TOWARDS PRINT MEDIA ADVERTISING” - SANTIKARY, DR.ARIJIT; Johar, Ms Damandeep (The journal of contemporary issues in business and government, 2023)
The purpose of this study is to look at the relationship between people's beliefs about print advertising, their attitudes about print advertising, and their intentions to act on those beliefs. Attitude is also looked at in this study. It looks at how attitude affects the relationship between belief factors and consumers' intentions to act. The Four belief factors are Credibility,Informative ,Attitude ,Hedonic/ Pleasure and Informational Responses. The study finds that Credibility,Informative,Attitude ,Hedonic/ Pleasure and Informational Responses have positive influences on consumers’ attitude and behavioral intention.Consumers' behavioural intentions are positively influenced by their attitude, according to the findings.. The target population for this study was people who have experience in searching for exposure to print advertising before. The respondents were classified according to their age, gender,occupation.The questionnaires were distributed to the respondents through online survey and questionnaire tool, Google Form. Implication are also discussed.